EFEKTIVITAS STRATEGI CLOZE STORY MAPPING TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS V DI SD 2 PADOKAN KASIHAN BANTUL - Danuri Danuri; Dwendha Lahitani (Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to determine the effectiveness of CSM strategies on comprehension reading skills in classes V Padokan 2 Elementary School. The research method used is a quasi-experimental method. In this study the subjects of the study were VA class students as the control class and V C as the experimental class with 28 VA and VC class students. Quantitative data analysis technique used is the calculation of independent sample t-test. Based on data analysis and discussion, researchers can conclude that CSM strategies are more effective than conventional methods of reading comprehension learning. The results of this study indicate that there is a significant difference between the experimental class and the control class as evidenced by the results of the independent sample t-test obtained by the value of Asymp. Sig (2-Tailed) 0.014 <0.05. CSM strategy is an effective learning strategy seen from the average value of the experimental class posstest which is 81.61 higher than the control class average value of 72.96.